Prognostic CT-imaging Findings for Complicated Acute Appendicitis : a Prospective Cohort Study - Kujala, Miska (My University, 2025)
Non-operative treatment of computed tomography (CT) -confirmed uncomplicated acute appendicitis is a safe and feasible alternative to surgery. Accurate pre- interventional differential diagnosis between uncomplicated and complicated acute appendicitis is essential to assess all available treatment options for patients with acute appendicitis. CT is the gold standard for diagnosing acute appendicitis and evaluating severity of the disease underlining the importance of potential CT findings associated with complicated appendicitis. The aim of this study was to assess potential prognostic CT factors for complicated acute appendicitis. A prospective cohort of patients with CT-diagnosed acute appendicitis was collected in concurrence with enrolment in two randomized clinical trials (APPAC II and III). Patients were included in this study, if they had a CT-confirmed acute appendicitis with both surgical and histopathological confirmation as a reference standard for the accurate as possible appendicitis diagnosis. The main aim was to evaluate the effect of appendiceal diameter on appendicitis severity and to identify a potential cut-off value predicting complicated acute appendicitis. The secondary aim was to identify other CT characteristics associated with complicated acute appendicitis such as appendiceal wall enhancement defect, and fluid and oedema around the appendix. A subgroup analysis was performed on patients without an appendicolith. A total of 3085 patients with CT-diagnosed appendicitis were included in the main analysis. In the subgroup analysis, there were 1965 patients without an appendicolith. In both analyses, wider appendiceal diameter (p<0.001), and appendiceal wall enhancement defect (p<0.001) were associated with increased risk of complicated acute appendicitis. No clear cut-off point for appendiceal diameter associated with complicated appendicitis could be determined. In patients without an appendicolith, appendiceal wall enhancement defect had an odds ratio (OR) of 3.39 (95%CI, 2.10- 5.50) for complicated acute appendicitis. Both a wider appendiceal diameter and appendiceal enhancement defect on CT are quite objective imaging findings associated with an increased risk of complicated acute appendicitis. Patients presenting with these findings on CT are at higher risk for complicated acute appendicitis and may not be optimal candidates for non-operative management of acute appendicitis. These results can guide clinicians in decision-making, when selecting optimal treatment alternatives for acute appendicitis.
Keywords: acute appendicits, CT imaging, appendiceal diameter